Redes sociales como estratégia de interacción del canal comunitario TV MICC. - González Ulloa, Elvia Marcela (2018)
The present research aims to direct the study of the use of social networks as an interaction strategy that the community media Tv MICC employs, for this research is intented to address from the branch of sociology and technology, because it’s the study is closely based on the study and behavior of the human being with the appearance of new technologies that facilitate and improve the communication process among the masses. This research work will address concepts related to television, social networks, web 2.0, community media in order to argue or sustain scientifically possible hypotheses or empirical knowledge that arise throughout the investigation. “social networks act as meeting points where it is possible to access information, share impressions, consult files and resources available in real time, such as Facebook, Twitter and YouTube” (Nass, 2011, p.133). In fact, social networks today play an important role in society; this is because human beings have adopted networks as an instrument that generates and has improved the communication process in society. Nowadays in Ecuador the community television media have used virtual platforms with the purpose of creating a new space for the dissemination of information for their audience, through WEB 2.0, a useful tool that has allowed the media to go up and share information in (audio potscats, video, text, photographs). For this research the qualitative methodology will be used; this will allow observing, describing and analyzing behaviors and attitudes of the people who have been considered for this study, the application of this methodology, will allow gathering information which is intended to contrast with the theoretical framework of this project, for this purpose it will make use of the matrix of content analysis and the realization of a focal group, the application of these instruments has allowed us to obtain relevant information from this means of communication, among which we identified the lack of economic and human resources that this channel has, a factor that prevents the proper use and management of the virtual pages that the medium has.